IMPROVING CHILDREN'S LABOR CHILDREN A THROUGH THE APPLICATION OF METODECANTOL ROUDHOH IN NURDZAKKY KIND OF DISTRICT CISARUA DISTRICT BANDUNG BARAT - rohaeti rohaeti (IKIP Siliwangi, 2018)
Research on improving the language ability of the children of Group A in Nurdzakky kindergarten, backed by less optimal child's language skills, and to know the planning of language ability improvement, learning process of cantol roudhoh method, and improvement of language ability after applying cantol roudhoh method using data collection technique observation, interview, and documentation. The subject of research is pre-school children kindergarten Nurdzakky, District Cisarua, West Bandung regency. Child language skills development data is collected through observation and field notes. Data analysis was done by descriptive analysis with result as follows, objective condition of development of language ability of child in Nurdzakky kindergarten, showed the ability of child language at the beginning of learning has not developed optimally, seen still less understanding story, mention syllable, mention words well, imitate mentioning sentences, imitating writing. The ability of the language of children shows only three (3) children out of ten (10) children who begin to develop, while as many as seven (7) children are still not developed, after the learning process by applying the cantol roudhoh method there are five (5) , four (4) children begin to develop, and one (1) children not yet developed, towards the end of semester 2 the development of children's language increased to seven (7) children have developed as expected, even there are two (2) children who develop very well, and one (1) developing child. The existence of a significant influence so that it can be argued that through learning methods of reading cantol roudhoh, can improve the language skills of children in kindergarten Nurdzakky.